PENGEMBANGAN MEDIA PETA HARTA KARUN: MENGENALKAN LAMBANG BILANGAN DAN HURUF PADA KELOMPOK B DI RAM NU 251 AL-FATTAH GRESIK - Nina Nuriyah Ma'arif; Lilis Nor Dayani; Riyadlotus Sholichah (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
In early childhood education (PAUD), teachers are required to carry out the learning process in a clear, interesting, fun, and educational manner. This can be done by using interesting and representative instructional media. This research focuses on the development of instructional media in order to introduce numbers and letters for pupils of Group B at RAM NU 251 Al-Fattah Gresik through the development of media "Peta Harta Karun". This research uses the five-step model of ADDIE, namely 1) analysis, 2) Design 3) Development, 4) Implementation, 5) Evaluation. Based on validation carried out by media material experts, media of peta harta karun has revealed that this instructional media has very good validity criteria and very feasible eligibility criteria, namely 82%. The results of the media expert's assessment received a score of 92% and are declared very valid and the assessment of treasure map media learning practitioners received a score of 93 (93%), so this media is considered very valid and very feasible.